Explaining collective violence in contemporary Indonesia from conflict to cooperation - Tadjoeddin, Mohammad Zulfan 1972- (Critical studies of the Asia-Pacific, 2014)
This book uniquely examines four types of violent conflicts pertinent to contemporary Indonesia framed in a theoretical approach of grievance, greed and social contract The overall process of democratization and decentralization has become a major force in catalysing the transformation of non-cooperative behaviours of secessionist and inter-ethnic violence to cooperative interactions of centreu2013regional relations and inter-ethnic political coalitions. Exploring secessionist, ethnic, routine-everyday and electoral violence conflict, Tadjoeddin seeks to discover what socio-economic development can do to overcome conflict and violence in Indonesia and make the country's transition to democracy safe for its constituencies This book will appeal to scholars of Development Studies, Political Economy and Indonesian Studies, as well as policymakers. --Provided by publisher